2020
DOI: 10.1186/s13075-020-02285-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of skin thickness and stiffness: the correlation with histology and clinical score in systemic sclerosis

Abstract: Background: Ultrasound is a useful tool to evaluate and quantify skin lesions. Few studies have assessed the criterion validity of skin ultrasound in systemic sclerosis (SSc). The aims of the study were to investigate skin thickness and stiffness using ultrasound and shear wave elastography (SWE) in SSc and to validate skin ultrasound measurements against histological skin thickness. Methods: A total of 22 patients with diffuse cutaneous SSc (dcSSc), 22 with limited cutaneous SSc (lcSSc), and 22 age-and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…This is a consistent finding across studies on HSCT for SSc, as skin thickness decreases significantly, especially in the first 6 months after HSCT [1,2,5,20,24,32]. Rodnan's score has good correlation with dermal thickness, evaluated both through skin biopsies and ultrasound [34,35]. In fact, histopathological analyses show a decline in dermal thickness at 1 year post-transplantation, which is not different from that of healthy controls at 5 years after HSCT [5].…”
Section: Discussionsupporting
confidence: 78%
“…This is a consistent finding across studies on HSCT for SSc, as skin thickness decreases significantly, especially in the first 6 months after HSCT [1,2,5,20,24,32]. Rodnan's score has good correlation with dermal thickness, evaluated both through skin biopsies and ultrasound [34,35]. In fact, histopathological analyses show a decline in dermal thickness at 1 year post-transplantation, which is not different from that of healthy controls at 5 years after HSCT [5].…”
Section: Discussionsupporting
confidence: 78%
“…According to several authors, the mRSS correlated more positively with skin stiffness than with its thickness [ 1 , 8 , 9 , 13 , 15 , 17 ]; therefore, it is important to test both modalities among a larger group of patients. Interestingly, some authors reported a significant correlation between mRSS and US measurements in the phalanx area [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that skin thickness (ST) measured with a US-based modality can replace mRSS examination [1,[9][10][11][12]. This is mainly because of the positive correlation between skin stiffness and the mRSS in these studies [1,11,[13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the skin stiffness at all Rodnan sites (p-value ≤ 0.001) (except in the fingers), in SSc patients - The % of the reduction in skin stiffness varied in the different Rodnan sites and in different phases of the disease. - There was a statistically significant change in the local Rodnan score only in the upper arm (p-value = 0.046) and forearm (p-value= 0.026) Chen (2020) 44 CC 44 (22dcSSc, 22lcSSc) 22 - Both Ultrasound-ST and skin stiffness were significantly higher in SSc patients (p-value < 0.001) and even higher in those with dcSSc, than in controls. - No clear correlation could be established between ultrasound-determined skin thickness and stiffness at the same site.…”
Section: Recent Acquisitions In the Use Of Elastography Ultrasound In The Study Of Skin In Systemic Sclerosismentioning
confidence: 95%